SFG Synthesis of General High-Order All-Pass and All-Pole Current Transfer Functions Using CFTAs - Worapong Tangsrirat (My University, 2014)
An approach of using the signal flow graph (SFG) technique to synthesize general high-order all-pass and all-pole current transfer functions with current follower transconductance amplifiers (CFTAs) and grounded capacitors has been presented. For general n th-order systems, the realized all-pass structure contains at most n + 1 CFTAs and n grounded capacitors, while the all-pole lowpass circuit requires only n CFTAs and n grounded capacitors. The resulting circuits obtained from the synthesis procedure are resistor-less structures and especially suitable for integration. They also exhibit low-input and high-output impedances and also convenient electronic controllability through thegm-value of the CFTA. Simulation results using real transistor model parameters ALA400 are also included to confirm the theory.
Keywords: Signal-flow graph; Analog and Mixed-Signal Circuit Design